Eye Exam in the Virtual World: A Pilot Study - Chen Ying-Ling; Shi Lei; W. L. Lewis J. (Journal of Ophthalmic Science, 2017)
This study investigated the feasibility of using three-dimensional (3D) technology as a multi-functional visual stimulus to assist the clinical eye exam. Specifically, we examined: (1) whether the receding movement of a 3D fixation target into distance could relax the accommodation of non-cycloplegic hyperopic subjects so that accurate refraction measurements could be achieved; (2) the feasibility of using the left-eye and right-eye images from the 3D monitor as the light source to perform swinging-flashlight pupil tests; and (3) the implementation of 3D technology to interrupt the binocular visual/motor fusion as required for the clinical cover test to identify strabismus. Using a 3D TV to provide visual stimuli and a photoscreening (PS) device, near-infrared (NIR) eye images were acquired and analyzed for each of the three objectives. The result of accommodation test showed that with visual stimuli, the maximal hyperopic refractions could more accurately suggest the patients’ true refractions and the more hyperopic patients responded more to the 3D projected distance. However the very mild hyperopia did not show significant response. The pilot tests also showed distinguishable normal and abnormal pupillary responses with 3D image illumination and also the difference in phoria and tropia in the ocular alignment test using 3D stimuli.
Keywords: 3D vision